The role of the complosome in health and disease - Xiao, Fang; Guo, Jixu; Tomlinson, Stephen; Yuan, Guandou; He, Songqing (Frontiers in Immunology, 2023)
The complement system is one of the immune system's oldest defense mechanisms and is historically regarded as a liver-derived and serum-active innate immune system that ‘complements’ cell-mediated and antibody-mediated immune responses against pathogens. However, the complement system is now recognized as a central component of both innate and adaptive immunity, at both the systemic and local tissue level. More recent findings have uncovered novel activities of an intracellularly active complement system—the complosome—that have shifted established functional paradigms in the field. The complosome has been shown to play critical function in regulating T cell responses, cell physiology such as metabolism, inflammatory disease processes, and cancer, which has amply proved its immense research potential and equally informed us that there is still much to learn about this system. Here, we summarize current understanding and discuss the emerging roles of the complosome in health and disease.